2003
DOI: 10.1021/jf0259359
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Parameters of β-Lactoglobulin−Pectin Complexes Assessed by Isothermal Titration Calorimetry

Abstract: Isothermal titration calorimetry (ITC) was used to determine the binding constant, stoichiometry, enthalpy, and entropy of beta-lactoglobulin/low- and high-methoxyl pectin (beta-lg-LM- and HM-pectin) complexes at 22 degrees C and at pH 4. The binding isotherms revealed the formation of soluble intrapolymer complexes (C1) further followed by their aggregation in interpolymer complexes (C2). The interaction between beta-lg and LM- or HM-pectin in C1 and C2 occurred spontaneously with a Gibbs free energy around -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 35 publications
9
105
1
1
Order By: Relevance
“…Consistent with this is the fact that pH w shows no temperature dependence, 27 and that mixing of BSA and PDADMAC by isothermal titration calorimetry at conditions of coacervation yields no heat. 68 On the other hand, complexation of b-lactoglobulin with pectin 69 or chitosan 70 is exenthalpic. The relative contributions of entropy and enthalpy for protein-polyelectrolyte complexation may be highly system-dependent as is the case for interpolyelectrolyte complexation, 71 but counterion release can be expected to contribute favorably in both cases, as well as in mesophase segregation, where the overall entropy reflects a delicate balance of the favorable effect of counterion release and the unfavorable restrictions on polymer configuration.…”
Section: Molecular Modelsmentioning
confidence: 99%
“…Consistent with this is the fact that pH w shows no temperature dependence, 27 and that mixing of BSA and PDADMAC by isothermal titration calorimetry at conditions of coacervation yields no heat. 68 On the other hand, complexation of b-lactoglobulin with pectin 69 or chitosan 70 is exenthalpic. The relative contributions of entropy and enthalpy for protein-polyelectrolyte complexation may be highly system-dependent as is the case for interpolyelectrolyte complexation, 71 but counterion release can be expected to contribute favorably in both cases, as well as in mesophase segregation, where the overall entropy reflects a delicate balance of the favorable effect of counterion release and the unfavorable restrictions on polymer configuration.…”
Section: Molecular Modelsmentioning
confidence: 99%
“…isothermal titration calorimetry (binding constant, stoichiometry, enthalpy, entropy), overlapping binding site model [15] Whey protein/gum arabic small angle X-ray scattering, turbidimetric titration [16] Silk fibroin/hyaluronic acid viscometry, turbidimetric titration, electrophoretic mobility [17] Instrumental methods…”
Section: Preparation Of Sf-ha Filmsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] These studies showed that soluble complexes, coacervates or precipitates formed when the pectin was mixed with the protein at pH values below and slightly above the protein's isoelectric point. The driving force for complexation was attributed primarily to electrostatic attraction between the anionic pectin and cationic patches on the protein surface, but hydrophobic forces were also thought to play a role for pectin molecules with higher degrees of methoxylation.…”
Section: Introductionmentioning
confidence: 99%
“…The driving force for complexation was attributed primarily to electrostatic attraction between the anionic pectin and cationic patches on the protein surface, but hydrophobic forces were also thought to play a role for pectin molecules with higher degrees of methoxylation. [18][19][20][21] The nature of the complexes formed depended on the linear charge density and hydrophobicity of the pectin molecules, as well as on the pH and ionic strength of the solution. 11,22 When pectin and β-lactoglobulin are mixed at neutral pH, and then the pH is reduced, one tends to observe soluble complex formation first, then coacervate formation, and finally precipitate formation, as the strength and number of electrostatic bonds increases.…”
Section: Introductionmentioning
confidence: 99%